2004
DOI: 10.1101/lm.65604
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and Serial Discriminations: A New Learning Paradigm to Assess Simultaneously the Effects of Acute Stress on Retrieval of Flexible or Stable Information in Mice

Abstract: The present study was aimed at simultaneously determining on the same subject, the effects of stress on retrieval of flexible (contextual or temporal) or stable (spatial) information. Three behavioral paradigms carried out in a four-hole board were designed as follows: (1) Simple Discrimination (SD), in which mice learned a single discrimination; (2) Contextual and Serial Discriminations (CSD), in which mice learned two successive discriminations on two different internal contexts; (3) Spatial Serial Discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…These findings are consistent with extensive previous evidence indicating that stress exposure or glucocorticoids administered systemically or into the hippocampus shortly before testing on a variety of learning tasks that differ in their behavioral demands, including water maze, inhibitory avoidance, and hole board, induce comparable temporary retention performance impairments (de Quervain et 2004; Célérier et al, 2004). Because those previous studies also reported that the same treatments administered before training do not affect either water maze acquisition or performance on a probe trial given immediately after acquisition, the findings strongly suggest that the GR agonist-induced retention impairment reflects a direct effect on retrieval of long-term memory.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with extensive previous evidence indicating that stress exposure or glucocorticoids administered systemically or into the hippocampus shortly before testing on a variety of learning tasks that differ in their behavioral demands, including water maze, inhibitory avoidance, and hole board, induce comparable temporary retention performance impairments (de Quervain et 2004; Célérier et al, 2004). Because those previous studies also reported that the same treatments administered before training do not affect either water maze acquisition or performance on a probe trial given immediately after acquisition, the findings strongly suggest that the GR agonist-induced retention impairment reflects a direct effect on retrieval of long-term memory.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, mice spontaneously expressed a specific delayed serial order memory retrieval pattern. Interestingly, using the 24-h RI, we showed that an acute stress (electric footshocks) delivered before the test session improved the retrieval of D2 but impaired the retrieval of D1 (Celerier et al, 2004;Chauveau et al, 2008). Thus, stress reversed the serial memory retrieval pattern and induced in parallel a rapid plasma corticosterone rise (Celerier et al, 2004;Chauveau et al, 2008).…”
Section: Introductionmentioning
confidence: 87%
“…In the CSD task, normal, nonstressed animals retrieved accurately both discriminations when the test session occurred shortly after acquisition (retention interval (RI) of 5 min); in contrast, they exhibited higher discrimination rates for discrimination 1 (D1) than for discrimination 2 (D2) when a 24-h RI was interpolated between the acquisition and test sessions (Celerier et al, 2004;Chauveau et al, 2008). In other words, mice spontaneously expressed a specific delayed serial order memory retrieval pattern.…”
Section: Introductionmentioning
confidence: 94%
“…First, data collection is entirely automatic, which generates strict and unbiased measurements of behaviour. Second, it allows the tests to be conducted in a soft light and silent atmosphere without human presence; thus, minimising stress for the mice (Célérier et al, 2004). Third, this method is particularly well suited for mice because it is based on the exploration of a novel environment, on locomotor activity and on head dipping in a hole-board, all of which are behavioural aptitudes spontaneously expressed by mice (Kliethermes and Crabbe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Before each mouse was tested, and between each phase of a test, the apparatus was cleaned with 50% ethanol and then with water. Photocells placed in each hole were used to automatically evaluate the number of sniff bouts (head dips) in each hole (Célérier et al, 2004). When only one hole was active (i.e.…”
Section: Apparatusmentioning
confidence: 99%